Loss of the ESX-5 secretion locus in Mycobacterium tuberculosis reshapes the mycomembrane and enhances ESX-1 substrate secretion - Benjamin Koleske; Saranathan Rajagopalan; Courtney Schill; Shichun Lun; Catherine Vilchèze; Lahari Das; Manish Gupta; Yazmin B. Martinez-Martinez; William R. Bishai; William R. Jacobs (Proceedings of the National Academy of Sciences, 2025)
The ESX-5 secretion system, uniquely found in slow-growing mycobacteria, is predicted to secrete over 150 proteins across the inner membrane of Mycobacterium tuberculosis ( M.tb ). Although many of these substrates are believed to promote M.tb virulence, most remain poorly characterized. Here, we use a complete locus deletion strain of ESX-5 in M.tb to examine the molecular changes caused by a broad loss in ESX-5 secretory substrates. We confirmed the selective loss of PE/PPE proteins secreted by ESX-5 into both the culture filtrate (CF) and outer mycomembrane (OMM) fractions of the M.tb ∆esx5 mutant. In examining other ESX systems, we found that ESX-1 substrate levels were increased in both the CF and OMM fractions of the ∆esx5 mutant. Conversely, the ESX-3 locus was transcriptionally repressed upon ESX-5 deletion. We noted that the ∆esx5 mutant had altered morphology in the form of wrinkled distortions of the bacterial surface. Likewise, we identified increased susceptibility of the ∆esx5 mutant to a variety of large (molecular weight >550 g/mol) antimicrobial compounds, suggesting that an intact ESX-5 system is required for M.tb to exclude such molecules. Our findings suggest that removing the ESX-5 system from M.tb fundamentally alters the properties of the mycobacterial OMM and impacts the expression and secretion activity of other ESX systems.